Exploring the anticancer potential of extracts and compounds from the heartwood of Cotinus coggygria Scop. wild growing in Serbia - Ivana Pašić; Miroslav Novaković; Vele Tešević; Slobodan Milosavljević; Nina Petrović; Tatjana Stanojković; Ivana Z. Matić (BMC Complementary Medicine and Therapies)
Abstract Background Cotinus coggygria has a long history of use in traditional medicine in Europe and Asia. The aim of study was to explore the cytotoxicity of extracts (EE-ethanol, MME-methylene chloride/methanol, and WE-water) and compounds (butin, butein, fisetin, sulfuretin, taxifolin, eriodictyol, fustin, cotinignan A, sulfuretin auronol, 3-O-methylepifustin, 3-O-methylfustin, and sitosterol-3-O-β-D-glucoside) isolated from C. coggygria. Mechanisms of anticancer effects of three extracts, butin, butein, and sulfuretin were examined. Methods Compounds were isolated from the EE using silica gel column chromatography and semipreparative HPLC. Structure elucidation was performed using NMR spectroscopy. Cytotoxicity was evaluated using MTT assay. The effects on cell cycle and cell death were investigated by flow cytometry. The antimigration effects were examined by scratch assay, while expression of the MMP2, MMP9, and VEGFA were measured by quantitative real time PCR. The antioxidant effects were examined by flow cytometry. Results 3-O-methylepifustin, epitaxifolin, and sulfuretin auronol were found for the first time in C. coggygria. The extracts and compounds showed selective cytotoxicity against HeLa, MDA-MB-231, HL-60, K562, A375, PC-3, and DU 145 cells. HeLa cells were the most sensitive to the cytotoxicity of MME (IC50 value of 47.45 µg/mL), while leukemia K562 and HL-60 cells were the most sensitive to the MME and EE (IC50 values in the range from 31.04 to 44.57 µg/mL). Butein exerted strong cytotoxicity on HeLa, K562, and MDA-MB-231 cells (IC50 values of 8.66 µM, 13.91 µM, and 22.36 µM). EE, butin, butein, sulfuretin, and fisetin were highly selective against leukemia K562 cells when compared with normal fibroblasts MRC-5 (selectivity index: 4.01, 5.15, 6.17, 7.05, > 4.41, respectively). Butein and fisetin showed high selectivity in the cytotoxic activity against HeLa cells when compared with MRC-5 cells (selectivity index: 9.91 and > 6.61). Three extracts, butin, butein, and sulfuretin, initiated apoptosis in HeLa cells by activating caspase-8 and caspase-9. The extracts, butin, butein, and sulfuretin inhibited HeLa cell migration. EE, MME, butein, and sulfuretin exerted cytoprotective effects in normal fibroblasts. Conclusions This research might suggest promising anticancer effects and underscores the need for additional research on C. coggygria extracts and compounds to assess their potential in cancer prevention and therapy.